Multisectoral nutrition planning in Nepal: Evidence from an organizational network analysis - Jenny Ruducha; Amiya Bhatia; Carlyn Mann; Harriet Torlesse (Wiley, 2022)
Abstract Multisectoral approaches are central to the global Scaling Up Nutrition (SUN) movement and the Sustainable Development Goals. Nepal joined SUN in 2011 and approved the first 5‐year Multisectoral Nutrition Plan (MSNP) in 2012, covering 2013-2017. This mixed methods study draws on organizational network analysis (ONA) and qualitative interviews with a sample of 22 organizations to examine (1) levels of engagement and network dynamics among government sectors and development organizations and (2) milestones and processes in the development and implementation of Nepal's MSNP. Findings suggest that the development of the MSNP was related to the high density of organizational connections; the leadership role of the Nepal's National Planning Commission and the National Nutrition and Food Security Secretariat; and the bridging roles played by a few government ministries and UN agencies that linked organizations that did not have direct relationships with each other. Specialized roles were observed for the three types of working relationships: policy dialogue, strategic planning and implementation. Partners were less connected on MSNP implementation than for policy dialogue and strategic planning, which may have constrained collaborative scale‐up efforts. The Ministry of Agricultural Development, in particular, was the conduit for connecting non‐health sectors into the broader network. Our study offers insights into the structure and dynamics of multisectoral planning in Nepal. It also contributes to a small but growing literature that illustrates how ONA can be applied to measure and use network results to elucidate the processes for strengthening multisectoral planning and implementation of nutrition‐specific and nutrition‐sensitive interventions.